Malcolm McDonald on marketing planning understanding marketing plans and strategy - McDonald, Malcolm (Kogan Page, 2017)
"A primer for marketing professionals and students, the second edition of Malcolm McDonald on Marketing Planning focuseson the practical application of marketing planning. Chapters explainadvertising and sales promotion strategies,price and sales strategies, how to define markets and segments, andhow to set marketing objectives and strategies. This fullyrevised second edition has not only been updated to contain the latest research, but also includes an extensive appendix covering topics such asdigital marketing, advertising, developing new products, and international product planning"--Provided by publisher.